Experimentelle Charakterisierung von Eisenoxid-Nanopartikeln aus Sprayflammen mit koaxialer Zweistoffzerstäubung - Tischendorf, Ricardo; Schmid, Hans-Joachim

PhASAR: An Inter-Procedural Static Analysis Framework for C/C++ - Schubert, Philipp; Hermann, Ben; Bodden, Eric (Proceedings of the 25th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS 2019), Held as Part of the European Joint Conferences on Theory and Practice of Software (ETAPS 2019))

Dynamische Simulation reaktiver Absorptionsprozesse zur Entwicklung modellbasierter Werkzeuge zur Vermeidung von Vor- und Notfallsituationen in der Industrie - Bothe, Mike; Fedorov, Alexander; Frei, Herrmann; Lutters, Nicole; Kenig, Eugeny

Logik im Logischen Empirismus - Peckhaus, Volker (Der Wiener Kreis – Aktualität in Wissenschaft, Literatur, Architektur und Kunst)

Identifikation und Kompensation produktionsbedingter Abweichungen im elektrischen Antrieb von Elektro- und Hybridfahrzeugen - Ott, M.

Self-sealing tool concept for RTM-processes - Stallmeister, Tim; Chalicheemalapalli Jayasankar, Deviprasad; Wang, Z.; Tröster, Thomas

Selbstabdichtendes Werkzeugkonzept für RTM-Prozesse - Stallmeister, Tim; Chalicheemalapalli Jayasankar, Deviprasad; Wang, Z.; Tröster, Thomas

End Group Stability of Atom Transfer Radical Polymerization (ATRP)-Synthesized Poly(N-isopropylacrylamide): Perspectives for Diblock Copolymer Synthesis - Herberg, Artjom; Yu, Xiaoqian; Kuckling, Dirk (Polymers)
Keywords: controlled radical polymerization; atom transfer radical polymerization; end group determination; N-isopropylacrylamide; block copolymerization; smart polymers; temperature sensitive polymers; lower critical solution temperature; ESI-TOF mass spectrometry; ion mobility separation; size exclusion chromatography

Dually Cross‐Linked Supramolecular Hydrogel as Surface Plasmon Resonance Sensor for Small Molecule Detection - Li, Jie; Ji, Chendong; Yu, Xiaoqian; Yin, Meizhen; Kuckling, Dirk (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Thermoresponsive Catechol Based-Polyelectrolyte Complex Coatings for Controlled Release of Bortezomib - Reis, Berthold; Vehlow, David; Rust, Tarik; Kuckling, Dirk; Müller, Martin (International Journal of Molecular Science)
Keywords: catechol chemistry; poly(caffeic acid); polyelectrolyte complex coatings; thermoresponsive coatings; controlled release; bortezomib; multiple myeloma

Azlactone-functionalized smart block copolymers for organocatalyst immobilization - Yu, Xiaoqian; Herberg, Artjom; Kuckling, Dirk (European Polymer Journal)
Keywords: Organic Chemistry; Polymers and Plastics; General Physics and Astronomy; Materials Chemistry

In vitro evaluation of innovative light-responsive nanoparticles for controlled drug release in intestinal PDT - Mahlert, Laura; Anderski, Juliane; Schoppa, Timo; Mulac, Dennis; Sun, Jingjiang; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)
Keywords: Light-responsive polymersPhotodynamic therapyControlled drug deliveryHT-29-MTX cellsIntestinal cancer

Light-Responsive Serinol-Based Polycarbonate and Polyester as Degradable Scaffolds - Sun, Jingjiang; Jung, Dimitri; Schoppa, Timo; Anderski, Juliane; Picker, Marie-Theres; Ren, Yi; Mulac, Dennis; Stein, Nora; Langer, Klaus; Kuckling, Dirk (ACS Applied Bio Materials)
Keywords: light-responsive polymers; biodegradable polymers; polycondensation

Preparation of Light-Responsive Aliphatic Polycarbonate via Versatile Polycondensation for Controlled Degradation - Sun, Jingjiang; Anderski, Juliane; Picker, Marie-Theres; Langer, Klaus; Kuckling, Dirk (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Liberating or indoctrinating? Surveying students’ perceptions of a Womens’ and Gender Studies requirement - Horwath, Ilona; Diabl, Christian (Gender and Education)
This article offers new insight into students’ responses to Womens’ and Gender Studies (WGS) classes by overcoming the self-selection bias hitherto inherent in the field. Exploring the experiences of 1406 students (770 women, 636 men) of a university with a WGS requirement across all study programmes, we examine the prevailing discourses on WGS, participants’ (dis)agreement as well as personal and professional benefits gained through WGS. Additionally, we evaluate the perceived value of WGS for themselves, in society, and of WGS opportunities in higher education. Findings reveal a gender bias regarding discourses, experience, benefit, and value, with 70.1% women and 32.4% men supporting the idea of WGS as a mandatory subject. Women’s support indicates a need for tools to negotiate gender issues, while men’s resistance serves to defend male privileges. We conclude that a requirement of WGS classes amplifies the potential for both – resistance and change.
Keywords: Education policy; equality; higher education; critical pedagogies; gender mainstreaming; curriculum

DEVELOPMENT OF A CYBER-PHYSICAL SIMULATION ASSISTANCE SYSTEM FOR PARTIALLY AUTOMATED OPTIMIZATION OF THE EXTRUSION PROCESS - Terhechte, Johannes; Berscheid, Anna Lena; Horwath, Ilona

Einleitung: Cyborgs revisited: Zur Verbindung von Geschlecht, Technologien und Maschinen - Berscheid, Anna Lena; Horwath, Ilona; Riegraf, Birgitt (Feministische Studien)

Phenomena of forming and failure in joining hybrid structures – Experimental and numerical studies of clinching thermoplastic composites and metal - Vorderbrüggen, Julian; Gröger, Benjamin; Kupfer, Robert; Hoog, Arne; Gude, Maik; Meschut, Gerson (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)

Investigations on a material-specific joining technology for CFRP hybrid joints along the automotive process chain - Vorderbrüggen, Julian; Meschut, Gerson (Composite Structures)

Plastic droplet welding: bond strength between plastic freeforming structures and continuous fiber-reinforced thermoplastic composites - Moritzer, Elmar; Hirsch, André; Heim, H.P.; Cherif, C.; Truemper, W. (Welding in the World)
Plastic freeforming (PF) is an additive-manufacturing process for producing three-dimensional plastic parts based on 3D CAD data by applying plastic droplets in layers. This process is used to produce customer-specific and complex geometries (prototypes and small series) on organic sheets. A comparable serial process is the injection of a second component onto organic sheets by injection molding. A sufficient bond between the PF structure and the organic sheets is of particular importance for each application. If this is not guaranteed, the composite system cannot withstand the mechanical load and fails. The force exerted on the system can no longer be transmitted between the PF structure and the organic sheet. The organic sheet is made of glass fiber-reinforced polypropylene (PP). The connection between the organic sheet and the PF structure is achieved by welding the molten polymer droplets and the surface of the organic sheet. The PF structures are made of PP to ensure sufficient compatibility with regard to the weldability of the components. The processing of PP in the PF process is a challenge because PP is a semicrystalline material. The shrinkage of semi-crystalline materials is significantly higher compared to amorphous materials. Due to the layered structure of the components, the shrinkage of the individual layers results in undesired warpage. The adhesive strength between the organic sheet and the PF structure is investigated by determining the bending strength in the 3-point bending test. The investigations include an optimization of the process parameters to maximize the adhesive strength. The experimental investigations show that an increase of the nozzle and build chamber temperature leads to a higher adhesive strength. In further investigations, the temperature of the nozzle shows no significant influence on the surface temperature despite the expected heat radiation. The surface temperature is almost only dependent on the temperature of the build chamber.

Development and Modeling of Design and Process Guidelines for FDM Structures for the Partial Reinforcement of Hybrid Structures - Moritzer, Elmar; Hirsch, André; Bürenhaus, Franziska Isabelle (AIP Conference Proceedings)
The mechanical properties of thin-walled plastic components are limited. One approach to improve the strength or stiffness of these components is to reinforce the thin-walled areas with an individually adapted Fused Deposition Modeling structure. Fused Deposition Modeling (FDM) is one of the most commonly used additive manufacturing processes. This process is characterized by the deposition of a fused, thermoplastic filament. Depending on the form of the reinforcement structure, the resulting hybrid structure should show higher strength or stiffness. The objective of the project is to determine constructive design and process guidelines for FDM structures. The FDM structure is to be used as a partial reinforcement for lightweight components and be adapted to the respective load conditions. Because of the lightweight application, the FDM structure should also have the lowest possible weight. The optimization of the FDM parts for different load cases is realized by adapting the design parameters. These parameters influence the layer generation and therefore also the inner structure of the FDM parts. In preliminary studies, the manufacturing restrictions of the FDM process are defined. The specimens are manufactured based on the Design of Experiments. To determine the static strength properties, different tests (tensile, compression, flexural, torsion and impact) are carried out. The investigations show that the filling strategy affects the mechanical properties. As a result of the investigations, design and process guidelines for the FDM structures are established according to the load conditions.

A Method to Evaluate the Process-Specific Warpage for Different Polymers in the FDM Process - Schöppner, Volker; Schumacher, C.; Fels, C. (AIP Conference Proceedings)
Additive manufacturing processes, like the Fused Deposition Modeling (FDM) process, do not need product-specific tools and create parts directly from the CAD data. In the FDM process, the semi-finished product, a wire of a thermoplastic polymer, is melted and forced through a nozzle. The continuous positioning of this nozzle allows the polymer to weld together strand by strand and layer by layer to produce a component. Because no mold is used in the FDM process, no holding pressure can be generated as in injection molding processes, in which the holding pressure is used to minimize the shrinkage and warpage of the part. In the FDM process, the part is generated in an ambient pressure environment. Each strand cools down and shrinks separately. This causes residual stresses in the part that can lead to major warpage and a complete stoppage of the process. This is the main reason why the material selection in the FDM process is restricted in comparison to conventional polymer processing technologies. In this paper, the warpage of different polymers is quantified as a criterion for evaluating the processability of polymers in the FDM process. Due to the process principle, the part properties in the FDM process are mainly influenced by the machine quality and the data processing, so that it is difficult to test a material for FDM independently of the machine and the data processing. Considering these influences, a custom-built specimen is created to test and quantify the warpage of different types of blended and reinforced polyamide 6. Considering the experimentally investigated warpage, the materials can be evaluated and the warpage can be related to the shrinkage investigated in pvT measurements. This procedure allows the machine- and process-independent rating of the processability in terms of warpage for different materials. Alongside other criteria, this is a necessary step to develop new materials with good processability in the FDM process.

Rissausbreitungsmechanismen in FDM-Verstärkungsstrukturen unter dynamischer Beanspruchung - Moritzer, Elmar; Hirsch, André; Paulus, S.
Das Fused Deposition Modeling (FDM) ist ein etabliertes additives Fertigungsverfahren zur Her-stellung von thermoplastischen Kunststoffbauteilen. In dem vorliegenden Beitrag sind FDM-Verstärkungsstrukturen aus dem Material Ultem 9085 dynamischen Langzeituntersuchungen un-terzogen worden. Dabei wurde die innere Struktur der Probekörper über eine Parametervariation verändert, sodass anschließend die signifikanten Einflussfaktoren auf die Langzeitfestigkeit un-ter dynamischer Belastung identifiziert und analysiert werden konnten. Mit dieser Vorgehens-weise sollte gleichzeitig eine Optimierung der FDM-Verstärkungsstrukturen hinsichtlich der dy-namischen Langzeiteigenschaften bei Biege- und Druckbelastungen vorgenommen werden. Des Weiteren sind anhand der Probekörper die auftretenden Bruch- und Rissausbreitungsmechanis-men analysiert worden. Anhand der ermittelten Wöhlerkurven kann die Lebensdauer unter dy-namischer Belastung abgeschätzt werden. Außerdem zeigen die Untersuchungen, dass Fehlstel-len durch eine hohe Strangbreite und Überfüllungen im Bauteil für Schwachstellen in den FDM-Verstärkungsstrukturen sorgen, an denen Risse bei Druckbelastung entstanden sind und sich dadurch schneller ausbreiten konnten.

Modellierung und Optimierung leistungselektronischer Konverter mit Halbleitern großer Bandlücke unter Verwendung kalorimetrischer Messverfahren - Bolte, Sven

Untersuchung des Verlustverhaltens eines geregelten und mit optimierten Pulsmustern gespeisten Hochgeschwindigkeits-Antriebssystems - Peter, Klaus
Hochgeschwindigkeitsantriebe kommen unter anderem in Vakuumpumpen, Turboradialverdichtern und Zentrifugen zum Einsatz und zeichnen sich typischerweise durch einen Betrieb mit konstanter Drehzahl über längere Zeiträume aus. Das in dieser Arbeit betrachtete Antriebssystem setzt sich aus einer permanentmagneterregten Synchronmaschine mit magnetgelagertem Rotor, einem LC-Filter, einem Wechselrichter in 2- oder 3-Stufen-Topologie, diverser Sensorik sowie einem Antriebsregler zusammen. In der vorliegenden Arbeit wurden Pulsmusterformen auf viertel- und halbschwingungssymmetrischer Basis ausgewählt und nach relevanten Kriterien wie die Eliminierung niederfrequenter Harmonischer oder die Minimierung des Oberschwingungsgehalts offline-optimiert. Hierzu wurde eine modifizierte Variante der Partikel-Schwarm-Optimierung verwendet. Ziel war die Substitution der trägerbasierten Dreiecksmodulation durch eine geeignete Modulatorstruktur zur Generierung und Ausgabe offline-optimierter Pulsmuster an den Wechselrichter. Im Verlauf der Arbeit wurde zudem herausgestellt, dass die herkömmliche feldorientierte Reglerstruktur nicht mit den optimierten Pulsmustern kombiniert werden kann, was auf die fehlende Pulssymmetrie und die abweichenden Kurzzeitmittelwerte der Schaltsignale von der Stellspannung im aktuellen Reglertakt zurückzuführen ist. Daher wurde eine modellbasierte Reglerstruktur, die zum Teil steuernden Charakter aufweist, entworfen und implementiert. Durchgeführte Messungen an einem Laststand mit einer Bemessungsleistung von 150 kW ergaben im maximal zulässigen Arbeitspunkt gegenüber der dreiecksmodulierten Pulsweitenmodulation eine Steigerung des Gesamtwirkungsgrads von bis zu 0,6% bei Verwendung eines 2-Punkt-Wechselrichters mit ausgangsseitigem LC-Filter.

Ein Beitrag zur Regelung von Permanentmagnet-Synchronmotoren in Statorflusskoordinaten ohne Rotorlagesensor - Pape, Thorsten

Optical transition between two optical waveguides layer and method for transmitting light - Hammer, Manfred; Förstner, Jens; Ebers, Lena
Die Erfindung betrifft einen optischen Übergang zwischen zwei optischen Schichtwellenleitern. Dazu ist eine Anordnung vorgesehen aus einem ersten optischen Schichtwellenleiter (2) und einem zweiten optischen Schichtwellenleiter (3), wobei der erste optische Schichtwellenleiter (2) und der zweite optische Schichtwellenleiter (3) voneinander verschiedene über ihre jeweilige Länge konstante Dicken (d, r) aufweisen, der erste optische Schichtwellenleiter (2) mit dem zweiten optischen Schichtwellenleiter (3) mittels einer optischen Schichtwellenleiterstruktur (4) verbunden ist, die über ihre gesamte Länge (w) eine Dicke (h) aufweist, die zwischen der Dicke (d) des ersten optischen Schichtwellenleiters (2) und der Dicke (r) des zweiten optischen Schichtwellenleiters (3) liegt. Erfindungsgemäß ist die Dicke (h) der optischen Schichtwellenleiterstruktur (4) über die gesamte Länge (w) der optischen Schichtwellenleiterstruktur (4) konstant. Damit wird eine Möglichkeit für einen effizienten und mit geringen Verlusten behafteten Übergang zwischen zwei optischen Schichtwellenleitern mit unterschiedlicher Dicke bereitgestellt.
Keywords: tet_topic_waveguides

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

'De triomf van de mens’ – kennis in 'Geschiedenis van een berg' - Lammer, Christina (Naar het onbekende: Perspectieven op literatuur, cultuur en kennis)

An Approach for Mapping Periodic Real-Time Tasks to Reconfigurable Hardware - Guettatfi, Zakarya; Platzner, Marco; Kermia, Omar; Khouas, Abdelhakim (2019 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW))

Konstruktionen des Terrors. Zur Hassrede in den Romanen Jenseits von Deutschland von George Tenner und Das dunkle Schiff von Sherko Fatah - Willeke, Stephanie (Hass/Literatur. Literatur- und kulturwissenschaftliche Beiträge zu einer Theorie- und Diskursgeschichte)

„So kommt doch alles noch zum Happy End.“ Sammy Gronemanns zionistische Komödie Der Prozess um des Esels Schatten - Willeke, Stephanie (Zwischen den Sprachen – Mit der Sprache? Deutschsprachige Literatur in Palästina und Israel)

Der eingehegte Terrorist? Dorothea Dieckmanns Guantánamo - Willeke, Stephanie (Das Politische in der Literatur der Gegenwart)

Portfolioarbeit als Professionalisierungsgelegenheit - Ballweg, Sandra (Portfolioarbeit im Kontext von Sprachenunterricht. Neue internationale Entwicklungen)

Das Verhältnis zwischen Fremdsprachenerwerbsforschung und Fremdsprachenunterricht - Einführung in das Themenfeld - Ballweg, Sandra; Riemer, Claudia (Dhoch3-Studienmodule Deutsch als Fremdsprache)

Theorien und Hypothesen für den L2-Erwerb - Einführung in das Themenfeld - Ballweg, Sandra; Introna, Silvia; Riemer, Claudia (Dhoch3-Studienmodule Deutsch als Fremdsprache)

Revealing the intrinsic geometry of finite dimensional invariant sets of infinite dimensional dynamical systems - Gerlach, Raphael; Koltai, Péter; Dellnitz, Michael (arXiv:1902.08824)
Embedding techniques allow the approximations of finite dimensional attractors and manifolds of infinite dimensional dynamical systems via subdivision and continuation methods. These approximations give a topological one-to-one image of the original set. In order to additionally reveal their geometry we use diffusion mapst o find intrinsic coordinates. We illustrate our results on the unstable manifold of the one-dimensional Kuramoto--Sivashinsky equation, as well as for the attractor of the Mackey-Glass delay differential equation.

Materials für inclusive mathematics education - Design principles an practices. - Häsel-Weide, Uta; Nührenbörger, M. (Proceedings of the Third International Conference on Mathematics Textbook Research an Development)

Fördern im inklusiven Mathematikunterricht im Spannungsfeld zwischen gemeinsamen Lernsituationen und gezielter Förderung. - Breucker, T.; Freesemann, O.; Häsel-Weide, Uta; Opitz, E. M.; Nührenbörger, M.; Wittich, C. (Zeitschrift für Heilpädagogik)

Das Zahlenbuch 4. Förderheft - Häsel-Weide, Uta; Nührenbörger, M.; Reinold, M.

Das Zahlenbuch. Förderkommentar Lernen zum 4. Schuljahr - Häsel-Weide, Uta; Nührenbörger, M.; Reinold, M.

Wille, Matthias, "Gottlob Frege. Begriffsschrift, eine der arithmetischen nachgebildete Formelsprache des reinen Denkens", Springer Spektrum: Berlin 2018 (Klassische Texte der Wissenschaft) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Honerkamp, Josef, "Denken in Strukturen und seine Geschichte. Von der Kraft des mathematischen Beweises", Springer: Berlin 2018 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Borrowing, Code-Switching and Fused Lects: Language Contact and Multilingual Prac-tices from a Socio-Historical Perspective - Ptashnyk, Stefaniya (Dimensionen des sprachlichen Raums: Variation - Mehrsprachigkeit - Konzeptualisie-rung (Schriften zur deutschen Sprache in Österreich))

Mediale (Selbst-)Referenzen in der galizischen Presse des 19. Jahrhunderts: „Gazeta Lwowska“ und „Lemberger Zeitung“ im Vergleich - Ptashnyk, Stefaniya (Mediale Selbstreferenzen)

„Stadtrechte und Stadtrechtsreformationen“. Tagung an der Heidelberger Akademie der Wissenschaften vom 03.04.2019 – 05.04.2019. Tagungsbericht - Ptashnyk, Stefaniya; Falkson, Katharina; Lemberg, Ingrid (HSozKult (online unter https://www.hsozkult.de/conferencereport/id/tagungsberichte-8281))

Jesseph, Douglas M., “Hobbes and the Syllogism”, in: Marco Sgarbi/Matteo Cosci (Hgg.), The Aftermath of Syllogism, Blumsbury Academic: London 2018 (Bloomsbury Studies in the Aristotelian Tradition), 67–81 - Peckhaus, Volker (Mathematical Reviews)

Tieszen, Richard, “Husserl and Gödel”, in: Stefania Centrone (Hg.), Essays on Husserl’s Logic and Philosophy of Mathematics, Springer: Dordrecht 2017 (Synthese Library; 384), 431–459 - Peckhaus, Volker (Mathematical Reviews)

Vanzo, Alberto, “Kant’s False Subtlety of the Four Syllogistic Figures”, in: Marco Sgarbi/Matteo Cosci (Hgg.), The Aftermath of Syllogism, Blumsbury Academic: London 2018 (Bloomsbury Studies in the Aristotelian Tradition), 157–190 - Peckhaus, Volker (Mathematical Reviews)

Lernumgebungen für den inklusiven Mathematikunterricht zwischen reichhaltiger Offenheit und fokussierter Förderung - Häsel-Weide, Uta (Zwischen Persönlichkeitsbildung und Leistungsentwicklung. Fachspezifische Zugänge zu inklusivem Unterricht)